Influence of the Vertical Position of Maxillary Central Incisors on the Perception of Smile Esthetics Among Orthodontists and Laypersons - Machado, Andre Wilson; McComb, Ryan W.; Moon, Won; Gandini, Luiz Gonzaga [UNESP] (Wiley-Blackwell, 2013)
Objective: The purpose of this study was to determine the perception of smile esthetics among orthodontists and laypeople with respect to different upper central incisor vertical positions in a frontal smile analysis.Materials and MethodsA frontal close-up smile photo of an adult Caucasian woman was selected. The patient had healthy upper anterior dentition and had no history of orthodontic treatment. Images were altered in order to create six different central incisor vertical positions in 0.5-mm increments. All images were assessed in three different views: full smile, gingival close-up excluding incisal edges, and incisal close-up excluding gingival margins. Images were randomly assembled in an album, which was given to 120 judges: 60 orthodontists and 60 laypersons. Each rater was asked to evaluate the attractiveness of the images using the visual analog scale. The data collected were then statistically analyzed.ResultsThe highest rated smiles showed two notable characteristics: the central-to-lateral incisal step was 1.5mm; and the central incisor gingival margins matched the laterals, and both were 0.5mm below the line of the canine gingival margins. The least attractive smile was the one with no step between the centrals and laterals, and with the central incisor gingival margins 1.0mm above the canine gingival margins.ConclusionThe results of this study indicate that slightly extruded upper central incisors are more esthetically preferred than intruded.Clinical SignificanceThe upper central incisors are the key determinant in evaluating smile esthetics, and thus, the assessment of their ideal vertical positioning is an aspect of paramount importance.